An anatomical investigation of jointed cactus (Opuntia aurantiaca, Lindley) with germination tests, and observations on the movements of the stomata - Archibald, E E A (Rhodes University, Faculty of Science, Botany Department, 1936)
From Introduction: In 1934 the Government started an active campaign on the eradiction of Jointed Cactus. This plant was causing considerable damage to the farms and commonages of the Eastern Province, and was spreading at an alarming rate. The Officer in Charge of eradication, Mr E. du Toit, was stationed at Grahamstown which is fairly centrally situated in the infested area. In 1935 Dr A. Leemann of the Division of Plant Industry made his headquarters at Rhodes University College.
Keywords: Cactus -- Anatomy; Opuntia; Stomata; Germination